Evidence of protein binding by a nucleopeptide based on a thyminedecorated L-diaminopropanoic acid through CD and In Silico studies - Roviello, Valentina; Musumeci, Domenica; Mokhir, Andriy; Roviello, Giovanni N. (Current Medicinal Chemistry, 2021)
Background: Nucleopeptides are chimeric compounds of biomedical importance carrying DNA nucleobases anchored to peptide backbones with the ascertained capacity to bind nucleic acids. However, their ability to interact with proteins involved in pathologies of social relevance is a feature that still requires investigation. The worrying situation currently observed worldwide for the COVID-19 pandemic urgently requires the research on novel anti-SARSCoV- 2 molecular weapons, whose discovery can be aided by in silico predictive studies. Objective: The aim of this work is to explore by spectroscopic methods novel features of a thymine-bearing nucleopeptide based on L-diaminopropanoic acid, including conformational aspects as well as its ability to bind proteins, starting from bovine serum albumin (BSA) as a model protein. Moreover, in consideration of the importance of targeting viral proteins in the current fight against COVID-19, we evaluated in silico the interaction of the nucleopeptide with some of the most relevant coronavirus protein targets. Methods: First, we investigated via circular dichroism (CD) the conformational behaviour of this thymine-bearing nucleopeptide with temperature: we observed CD spectral changes, particularly passing from 15 to 35 °C. Scanning Electron Microscopy (SEM) analysis of the nucleopeptide was also conducted on nucleopeptide solid samples. Additionally, CD binding and preliminary in silico investigations were performed with BSA as a model protein. Moreover, molecular dockings were run using as targets some of the main SARS-CoV-2 proteins. Results: The temperature-dependent CD behaviour reflected the three-dimensional rearrangement of the nucleopeptide at different temperatures, with higher exposure to the solvent of its chromophores at higher temperatures compared to a more stacked structure at a low temperature. SEM analysis of nucleopeptide samples in the solid-state showed a granular morphology, with a low roughness and some thread structures. Moreover, we found through spectroscopic studies that the modified peptide bound the albumin target by inducing significant changes to the protein secondary structure. Conclusion: CD and preliminary in silico studies suggested that the nucleopeptide bound the BSA protein with high affinity according to different binding modes, as testified by binding energy scores lower than -11 kcal/mol. Interestingly, a predictive study performed on 3CLpro and other SARS-CoV-2 protein targets suggested the potential ability of the nucleopeptide to bind with good affinity the main protease of the virus and other relevant targets, including the RNAdependent RNA polymerase, especially when complexed with RNA, the papain-like protease, and the coronavirus helicase at the nucleic acid binding site.
CRIS-Team Scopus Importer:2021-08-27
Keywords: 3CLpro; CD; Coronavirus infections; COVID-19; Nucleopeptide; Pandemics; Protein binding; RNA-protein complex; SARS-CoV-2; SEM